(untitled) (Revista de Biología Marina y Oceanografía, 2020)
Osteological development of the vertebral column, caudal complex and median fins in larvae of the bullseye puffer fish, Sphoeroides annulatus, were studied using specimens cleared and double stained for bone and cartilage. The first cartilaginous structures appeared 10 days (4.2 mm NL) after hatching and by day 28 (14.9 mm TL) most of the bone elements had already formed. Sphoeroides annulatus exhibited fusion of bone elements, the same as other Tetradontiformes, one of the most evolved teleosts.